Family history of diabetes mellitus determines insulin sensitivity and ß cell function in polycystic ovary syndrome - Vrbíková, Jana; Grimmichová, Tereza; Dvořáková, Kateřina; Hill, Martin; Stanická, Soňa; Vondra, Karel (Physiological research, 2008)
Objective: To examine the impact of family history of diabetes mellitus 2 (DM 2) on insulin sensitivity and secretion in lean women with polycystic ovary syndrome (PCOS). Thirteen healthy women (C), 14 PCOS without family history of DM 2 (FH-) and 8 PCOS with family history of DM 2 (FH+) were examined using euglycemic hyperinsulinemic clamp and an arginine secretion test (insulin and glucagon at fasting glycemia (AIRFG and AGRFG) and at hyperglycemia (AIR14 and AGR14)). FH+ women were more insulin resistant than FH- with lower insulin sensitivity index corrected per lean body mass (p<0.05). They had significantly higher triglycerides (p<0.05) and lower HDL-cholesterol (p<0.05) than C or FH- women. Concerning insulin secretion, AIRFG was increased in FH+ women comparing FH- women (p<0.05). Disposition indices derived from AIRFG or AIR14 and insulin sensitivity index did not differ between FH+ or FH-. Thus, women with PCOS with the concomitant family history of DM 2 have lower insulin sensitivity than healthy control women. Insulin resistance observed in these women with PCOS is compensated by increased insulin secretion.
Keywords: dospělí; homeostáza; Glucagon-Secreting Cells; Female; Anthropometry; Adult; ženské pohlaví; Arginine; Diabetes Mellitus, Type 2; diabetes mellitus; Insulin secretion; beta-buňky; lidé; Blood Glucose; Hormones; Homeostasis; diabetes mellitus 2. typu; antropometrie; glykemický clamp; krevní tlak; syndrom polycystických ovarií; Humans; Polycystic Ovary Syndrome; Insulin Resistance; index tělesné hmotnosti; Insulin-Secreting Cells; inzulinová rezistence; arginin; Diabetes Mellitus; Insulin resistance; hormony; Polycystic ovary syndrome; Blood Pressure; Body Mass Index; Glucose Clamp Technique; krevní glukóza; buňky vylučující glukagon